2015
DOI: 10.1128/aac.04122-14
|View full text |Cite
|
Sign up to set email alerts
|

Activity Spectrum of Colicins Produced by Shigella sonnei and Genetic Mechanism of Colicin Resistance in Conspecific S. sonnei Strains and Escherichia coli

Abstract: Colicin-mediated killing is an example of allelopathy, which has been found among several bacteria. Screening of 42 strains of Shigella sonnei isolated from diarrheal patients revealed that 39 (93%) S. sonnei strains were positive for colicin production against Escherichia coli DH5␣. In the PCR-based detection of the colicin types, 36 (92.3%) were identified as E3, 2 (5.1%) as E3 and E8, and 1 (2.6%) as E3 and E2. Representative S. sonnei strains producing heterologous colicins exhibited antagonism against dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…A further pivotal event in the emergence of this Central Asia clade prior to its introduction into Bhutan was the fixation of the previously described E-type colicin plasmid pSSE3 (with 100 % identity in DNA sequence). This E-type colicin has been shown to be antagonistic against a variety of diarrhoeogenic E. coli , but not against commensal E. coli ( Calcuttawala et al , 2015 ). Plasmid pSSE3, which was found in all Bhutanese isolates ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A further pivotal event in the emergence of this Central Asia clade prior to its introduction into Bhutan was the fixation of the previously described E-type colicin plasmid pSSE3 (with 100 % identity in DNA sequence). This E-type colicin has been shown to be antagonistic against a variety of diarrhoeogenic E. coli , but not against commensal E. coli ( Calcuttawala et al , 2015 ). Plasmid pSSE3, which was found in all Bhutanese isolates ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Strains that are capable of producing a colicin are better able to compete against colicin sensitive strains over ecological niches. In the case of S. sonnei , it has been reported that up to 93% of tested strains in Kolkata, India, harbor at least one colicin-encoding plasmid which were shown to target closely related susceptible E. coli strains, which as previously mentioned, were important for restricting Shigella colonization (Calcuttawala et al, 2015 ). Meanwhile, the chromosomally encoded O-antigen chain length regulator WzzB was recently reported to contribute to colicin E2 resistance in S. flexneri (Tran et al, 2014 ).…”
Section: First Barriers To Shigella Infection: the Microbiota And Thementioning
confidence: 93%
“…It derives its energy for transport by interacting with the trans-periplasmic membrane protein TonB. 44 Coincidently, BtuB also acts as the receptor for the proteinaceous antibacterial A and E colicins. 45,46 We speculate that this transporter could contribute to entry of L-5b into the periplasm.…”
Section: Ehec Sakai Mutants Exhibiting Increased Tolerancementioning
confidence: 99%